Prevalence and outcomes of pregnancy-induced hypertension among women seeking maternity services in selected tertiary hospitals of Gandaki Province - Gurung, Bandi; Thapaliya, Rekha; Adhikari, Rajesh (Journal of Gandaki Medical College-Nepal, 2025)
Introduction: Pregnancy-induced hypertension (PIH), particularly pre-eclampsia and eclampsia, significantly contributes to maternal and perinatal mortality globally. This study aimed to assess the prevalence and outcomes of PIH among women seeking maternity services in tertiary hospitals in Gandaki Province. Methods: A retrospective research design was adopted, using a census method. The secondary data of women seeking maternity services in selected tertiary hospitals of Gandaki Province between Shrawan 2079 to Ashad 2080 was included in the study. Medical records and logbooks were reviewed, focusing on 751 women diagnosed with PIH. Data were analyzed using descriptive statistics. Results: Out of 11,927 women, 751 women seeking maternity services in Gandaki province had PIH. More than half (53.4%) had gestational hypertension, 35% had pre-eclampsia, 6.5% had eclampsia, and 5.1% had chronic hypertension with superimposed pre-eclampsia. Regarding maternal outcomes, 11.5% had pre-labour rupture of membrane, 1.3% had postpartum hemorrhage, 0.9% had abruptio placenta, and 0.3% had acute respiratory distress syndrome. Likewise, 18.5% had fetal distress, 13.6% had oligohydramnios, 8% had intrauterine growth retardation and 3.1% was intrauterine fetal death or still death. Twenty-five percent had prematurity, 31.4% had low birth weight, and 19.6% were admitted to the newborn intensive care unit. In the study, 0.1% of maternal deaths and 1.6% of neonatal deaths were found in women with PIH. Conclusions: The prevalence of PIH was nearly one-tenth among women seeking maternity services, affecting both maternal and fetal outcomes. Gestational hypertension was the most common type. Implementing awareness programs focused on early diagnosis and treatment of PIH is recommended for better outcomes.